Congenital factor XI deficiency, complete genotype and phenotype of two Iranian families. Issue 8 (December 2019) - Dorgalaleh, Akbar; Gholaminezhad, Masoume; Shiravand, Yavar; Naderi, Majid; Safa, Majid
Abstract : N/A: Congenital factor XI (FXI) deficiency is a mild trauma-related bleeding disorder with estimated worldwide prevalence of one per 1 million. The disorder is less frequent in Iran and a few studies have been performed on Iranian patients. In the current study, we assessed molecular, laboratory and clinical features of two Iranian patients with congenital FXI deficiency and their families. Clinical features and demographic data of the patients were assessed by the physician and a staff member trained specifically to deal with patients with bleeding disorders. FXI activity and antigen assays were performed for seven members of the two families and genotyping was performed by direct sequencing of all F11 gene exons and intron-exon boundaries as well as the untranslated regions. Five members of the two families were affected by FXI deficiency. Both patients experienced prolonged epistaxis, whereas other family members were asymptomatic. Two gene defects were observed in the patients and their families. Two disease-causing mutations were c.943G>A (p.Glu315Lys) missense and the four-nucleotide deletion (g.27849-27852del) in exon 15. The gene deletion was observed in homozygote state in the patient with severe FXI deficiency (FXI activity <1%) and heterozygote state in the parent, whereas the c.943G>A mutation was detected in heterozygote state and was accompanied by epistaxis in the patient. FXI deficiency is a mild bleeding disorder that is caused by heterogeneous molecular defects.